Valsartan: come versatilità e tollerabilità possono contribuireal contenimento della spesa sanitaria - Costa, Francesco Vittorio (Farmeconomia. Health Economics and Therapeutic Pathways, 2011)
The search for a more specific and complete blockade of the hypertensive effects of angiotensin and of better tolerability than ACE-inhibitors has led to the development of angiotensin II receptor blockers (ARBs). ARBs have been evaluated in several large studies in terms of efficacy and safety in reducing blood pressure, as well as for cardiovascular and renal protection. Among angiotensin II receptor blockers, valsartan and losartan have the greatest number of therapeutic indications. In light of the costs related to cardiovascular disorder valsartan represents a potential long-term health cost saving strategy. Furthermore valsartan shows one of the lowest costs for patient achieving blood pressure goals and the higher level of persistence in its class.